2010
DOI: 10.1159/000278747
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Green Tea, Chokeberry and Honeysuckle Polyphenols on Nutrients and Mineral Absorption and Digestibility in Rats

Abstract: Background/Aims: Natural polyphenols are chemically and biologically active. This study aimed at examining the physiological effects of high doses of polyphenol extracts from green tea and new polyphenol-rich sources (chokeberry and honeysuckle fruits) on nutrient absorption. Methods: 32 male Wistar rats were divided into four groups and fed a diet supplemented with one of the three polyphenolic extracts (at 0.4%) or a control diet for 4 weeks. A perfusion technique was used to study the effects at intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…However, our results showed that neither extract had an effect on bone mineralization, which is not consistent with previous findings. Frejnagel and Wroblewska (2010) reported similar results, showing that green tea, chokeberry, and honeysuckle polyphenols reduced Zn and Cu absorption in rats, but this was not accompanied by diminished concentrations of the femur bone. Different fatty acid compositions in the diets did not affect the tibia characteristics, which is consistent with the findings of other studies reporting no effect of the FA composition on bone characteristics in poultry.…”
Section: Pinteraction Walnut Oilmentioning
confidence: 58%
“…However, our results showed that neither extract had an effect on bone mineralization, which is not consistent with previous findings. Frejnagel and Wroblewska (2010) reported similar results, showing that green tea, chokeberry, and honeysuckle polyphenols reduced Zn and Cu absorption in rats, but this was not accompanied by diminished concentrations of the femur bone. Different fatty acid compositions in the diets did not affect the tibia characteristics, which is consistent with the findings of other studies reporting no effect of the FA composition on bone characteristics in poultry.…”
Section: Pinteraction Walnut Oilmentioning
confidence: 58%
“…While less is known about the effects of polyphenol-rich plant products in pigs, studies in broilers have shown that plants rich in polyphenols can also influence the microbial composition in a beneficial manner [5]. However, there are also some studies in broilers, mice and rats which exerted adverse effects of polyphenols on nutrient transport in intestinal cells [6-8] and on apparent total tract digestibility of nutrients [8,9]. Thus, the aim of the present study was to investigate the hypothesis that feeding plant products rich in polyphenols not only influences the expression of pro-inflammatory genes and the villus height:crypt depth ratio in the intestine of pigs but might also influences the microbial composition and the expression of nutrient transporters in the intestine and the digestibility of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that polyphenols might recover the digestibility of nutrients owing to the increase in absorptive surface of the intestine [30]. Similar con- clusions were drawn by Frejngel and Wroblewska, who examined the physiological effect of high doses of polyphenol extracts from green tea on nutrient absorption and digestibility in rats [31].…”
Section: A B C D Discussionmentioning
confidence: 52%